Comparison of indigenous and scientific knowledge on soil classification among farmers in Imugan, Nueva Vizcaya, Philippines - Martin, Hannie T. (2016)
The study was conducted to verify the application of indigenous knowledge of Imugan farmers in soil classification in the Imugan watershed of Sta Fe, Nueva Vizcaya. The results were further compared with the scientific knowledge on soil classification. Drawing out the indigenous knowledge was made through the use of participatory rural appraisal techniques such as focus group discussions, key informant interview, and transect walk. Field observation was also done. On the other hand, scientific knowledge included soil profiling, characterization and soil laboratory analysis. Criteria used by Imugan farmers in soil classification are their experiences supported by their ability to observe attributes of soil resource. This is their way to identify the best use, and appropriate management practices of the soil resource. Scientific soil classification system is a through process of soil characterizations that investigates not only the surface soil's properties, its genesis and chemical properties but also subsoil's characteristics. This expensive and rigorous procedure is intended to aid decision making on the land's best use and crop choice. The two systems of soil classification-knowledge that is tested through time combined with knowledge formed from scientific analysis - may have differences, but combining them together in the framework of soil classification will benefit Imugan farmers. The combined system of soil classification provide detail information about nutrients deficiency and attributes of each soil type, variety of crops suitable for each soil based on farmers' preference and appropriate inputs in raising crops that are less or not suitable in a given soil.
Keywords: Agriculture